Consumer intention to use QR code - Tze, Yien Chen; Wei, Shen Ng; Wei, Ling Tan; Yan, Ying Tan; Pui, Yee Lee (IGI Global, 2016)
This study examines how the users' perception of QR code affects their attitude towards QR code, particularly in the context of Malaysian local university students. Next, the study examines the relationship between their attitude towards QR code and their intention to use the QR code. Empirical analysis via multiple regression analysis affirmed that PIQ influences PU and PSQ influences PEoU. Additionally, both PU and PEoU influences the attitude of users, which leads to the influence of attitude towards the user's intention to use to QR code. The functionality of QR codes can be utilized by business entities to serve for their company and create revenue. However, the companies must modify the content of the QR code application according to the minimum requirements and perception of the users. The results of this research offer essential guidelines for companies to tailor the information of their campaigns to the users' preferences. Next, future researches can utilize the proposed theoretical framework to exploit the potentials of QR code in the marketing field.